Distinctive Characteristics of Its Principal Components (Diversity Research: Journal of Analysis and Trends, 2023)
The article talks about Muvashshah poems of Muhammad Aminkhoja Muqimi, their specific features. Muvashshahs are important in studying the literary and aesthetic world of poets. Studying them on a scientific basis serves to a certain extent in illuminating the dark aspects of the history of literature